2019
DOI: 10.7196/samj.2019.v109i6.14002
|View full text |Cite
|
Sign up to set email alerts
|

Rational use of the fluoroquinolones

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…Specifically, application of Clinical Laboratory and Standards Institute breakpoints in clinical practice has shown little activity of FQs 21 , 22 , and there is potentially mild antagonism between FQs and CAM in combination therapies 17 . Moreover, FQs have received warnings from the US Food and Drug Administration and the European Medicines Agency for significant adverse effects, including peripheral neuropathy, psychosis, hypoglycaemia, tendon rupture, and aortic dissection 23 . Recently, Khadawardi et al 24 reported that substitution of RFP or EB with FQs resulted in similar treatment outcomes compared with standard triple-drug regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, application of Clinical Laboratory and Standards Institute breakpoints in clinical practice has shown little activity of FQs 21 , 22 , and there is potentially mild antagonism between FQs and CAM in combination therapies 17 . Moreover, FQs have received warnings from the US Food and Drug Administration and the European Medicines Agency for significant adverse effects, including peripheral neuropathy, psychosis, hypoglycaemia, tendon rupture, and aortic dissection 23 . Recently, Khadawardi et al 24 reported that substitution of RFP or EB with FQs resulted in similar treatment outcomes compared with standard triple-drug regimens.…”
Section: Discussionmentioning
confidence: 99%
“…There are some restrictions in place at present, like the prohibited prescription of ciprofloxacin for complicated UTIs, but controls must become more widespread to make a greater impact [198]. There have recently been restrictions placed on the use of FQs for mild bacterial infections, but this is due to potential side effects and not for antimicrobial resistance reasons [199]. Alongside this, the evidence that the misuse and sublethal exposure of FQs is potentially leading to an increase in mutagenesis and resistance to other antibiotics is of concern.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The systemic fluoroquinolones (FQs) have been used for >30 years for a variety of infectious conditions, and have been among the most wide ly prescribed antibiotics globally (Richards et al, 2019).…”
mentioning
confidence: 99%